Peer Assessment - A Way to Enhance Students’ Learning Capacity - Jiang, Lai; Ho, Hoai Nam; Nguyen, Thi Le; Nguyen , Minh Son; Phan, Thi Huong; Pham , Ngoc Hoa; Vo, Thi Nga (Journal of Technical Education Science, 2022)
The goal of the EMVITET project is to support lecturers in creating a student-centered and competence-based learning environment in the direction of Education 4.0, whereby assessment is considered a way of learning. This article explains the importance of “assessment as learning” and illustrates how to implement this concept through five cases from project partner colleges and universities, where peer assessment was implemented in class sizes with a maximum of 70 students. All case descriptions follow the same structure: First, contextual information and rationale of peer assessment are given. It is followed by a description of how peer assessments were organized. Finally, the observable impact was also mentioned with available data. Through the analysis of typical cases, the authors offered key principles for implementing peer assessment successfully: (1) Clarify the purposes and expectation of peer assessment; (2) Pay enough time and attention to the design of the evaluation criteria; (3) Anonymize peer assessment so that students feel comfortable evaluating each other; (4) Ensure multiple peer assessors to reach a higher reliability and validity - ensure each student is assessed by at least two or three fellow students. More importantly, the article also suggests: the lecturer gives students more responsibility and control, and the degree of the giving responsibility and control shall match the learning goals and level of students’ prior knowledge and their learning ability. With the wonderful impacts of peer assessment, most students expect the method to be applied widely and it is highly recommended to be continued in the near future.